The Effect of Land Use Changes on Landslide in the High Slope Area at Surat Thani Province - ผ่องพุฒิ ณัฐณิชา; ผิวนิล อรอนงค์; จันทร์แก้ว เกษม; รัตนเสริมพงศ์ สุรชัย (KKU Science Journal, 2016)
This research aimed to analyze the changes in land use and predict future land use by using IDRISI and Land Change Modeler to examine areas of landslide risk in the steep slope area in Surat Thani Province. The study found that, during the years 2000-2013, forest area had been decreased continuously, while area of para rubber plantations increased. Some areas of para rubber plantations were located on slopes steeper than 30 degrees, and had improper planting methods which were vulnerable to landslides. Moreover, an increase in residential areas were found during the years 2002-2005, and number of wells also raised during the years 2005-2007. There was a decrease in mixed orchard area; on the other hand, area of oil palm plantations had been increased in the year 2010. The projection of changes in land use of the year 2018 showed that the forest and mixed orchard areas will reduce. Conversely, the areas of oil palm and para rubber plantations, and residence will be increased. Mitigation of the impact of landslides caused by human action needs active actions for proper land utilization, and plants para rubber in the steep slope area under the principles of soil and water conservation.